Writing off Indonesia’s forestry debt: how the IMF, the Indonesian Bank Restructuring Agency and Bank Mandiri are financing forest destruction - Barr, C.; Setiono, B. (2003)
Bank Mandiri, the largest bank in Indonesia, was the latest government institution to provide financial subsidies to Indonesian forestry conglomerates by writing off major part of their debts. Before Bank Mandiri, IBRA, under the pressure by the IMF for the “quick sales” of its assets, had written off debts of these forestry companies, in the amount of billions of US dollars. Previously, these forestry companies had grown rapidly, without regard to sustainable forests, due to Suharto's forest subsidies. These latest capital subsidies will encourage the companies to undervalue the forests they are charged with managing, and this will lead to continued high level forest destruction-paid for with public money.